Influencia de la enseñanza con entornos virtuales en la autoeficacia académica en estudiantes de la Facultad de Ciencias Económicas y de Negocios Universidad Nacional de la Amazonía Peruana Iquitos 2023 - Pérez Reátegui, Jorge Alberto (2024)
The main objective of this study was to explain the influence of teaching through virtual environments on the academic self-efficacy of students from the Faculty of Economics and Business of the National University of the Peruvian Amazon, in Iquitos in 2023. An explanatory research methodology was employed with field, bivariate, and cross-sectional designs. The sample consisted of 348 university students, who were administered a survey composed of two questionnaires previously validated through expert analysis of items, construct, and reliability. The results of the simple regression analysis indicate that 33.9% of the variability in academic self-efficacy can be attributed to the influence of the teaching variable with virtual environments, according to the coefficient of determination (R2). Individual parameter contrasts confirm this positive and significant influence. Additionally, it was found that the same variable has a significant effect on the academic self-efficacy of university students, as evidenced by a p-value of .000, below the significance level of .05, leading to the rejection of the null hypothesis and the acceptance of the alternative hypothesis. It is concluded that these results suggest that activities related to teaching through virtual environments have a positive influence on the academic self-efficacy of university students in the specific context mentioned.